Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
In this case, we'll have to carry out several steps to find the solution.
Step 01:
data:
f(x)= -3x³ - 8x² - x + 8
g(x)= 3x³ - 6x² - 8x - 8
Step 02:
functions:
(f - g)(x):
(f - g)(x) = -3x³ - 8x² - x + 8 - (3x³ - 6x² - 8x - 8)
(f - g)(x) = -3x³ - 8x² - x + 8 - 3x³ + 6x² + 8x + 8
(f - g)(x) = - 6x³ - 2x² + 7x + 16
(f - g)(-1):
(f - g)(-1) = - 6(-1)³ - 2(-1)² + 7(-1) + 16
(f - g)(-1) = - 6(-1) - 2(1) + 7(-1) + 16
(f - g)(-1) = 6 - 2 - 7 + 16
(f - g)(-1) = 13
That is the full solution.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.